PREGNANCY MANAGEMENT IN PATIENTS WITH MESENCHYMAL DYSPLASIAS - L. S. Radetskaya; A. D. Makatsaria; V. D. Bitsadze; M. O. Udovichenko (IRBIS LLC, 2017)
The article presents an overview and results of clinical research of rare but very important diseases - mesenchymal displasias including Marfan syndrome, Ehlers-Danlos (EDS) syndrome, Osler-Weber-Rendu disease. The basic component of these diseases is the hereditary connective tissue disorder. Patients may have different symptoms, because various organs may be involved: skeletal, ocular, cardiovascular systems etc. The diagnosis is based on the clinical criteria and molecular tests. The pathogenesis of these disorders has not been fully elucidated. Pregnancy usually increases the risk of life threatening complications. Early diagnosis and multidisciplinary management of pregnancy and delivery are essential for good outcomes. The aim of this study was to evaluate the course of pregnancy and the delivery outcome in patients with mesenchymal dysplasias. Materials and methods. Fifty six pregnant women with mesenchymal dysplasias (23 with Marfan syndrome, 22 with Ehlers-Danlos syndrome, 11 with hereditary hemorrhagic telangiectasia - HHT) were examined in a specialized cardiological maternity ward. The patients underwent physical examination, routine laboratory tests, hemostasis tests, ECG, echocardiography, MRI, X-ray examination, and pulse oximetry. Results. All patients had hemorrhagic complications of various localization; 18 women with Marfan syndrome had aggravated mitral regurgitation, 10 - aortic insufficiency, 13 - mitral valve insufficiency. One patient with Marfan syndrome died because of aortic dissection on day 45 upon delivery. Pulmonary arteriovenous malformations were found in 10 patients with HHT; the symptoms of hypoxemia developed in 6 HHT patients who were diagnosed with right-to-left blood shunting. One patient with HHT developed the symptoms of vena cava inferior compression caused by an aneurism in the truncus brachiocephalicus. Forty patients showed abnormal hemostasis results (platelet dysfunction - 38 patients; DIC syndrome - 31). Cesarean section was performed in 53 patients. Vaginal delivery (3 patients with EDS) was complicated by massive postpartum hemorrhage and deep vaginal tears. Conclusion. Patients with mesenchymal dysplasias are under increased risk of different complications during pregnancy and delivery; they need multidisciplinary management and repeated hemostasis testing. Cesarean section is the preferred method of delivery in such patients.